Changing patterns of heart disease complicating pregnancy in the University Obstetrics and Gynaecology Unit, Colombo - Kaluarachchi, A; Wijerathne, C N; Senevirathne, H R (My University, 2012)
Institution: Department of Obstetrics and Gynaecology, Faculty of Medicine, University of Colombo. Introduction: The incidence of rheumatic heart disease in pregnancy has declined in developing countries in association with improved socio - economic conditions. Objective: To study the changes in the pattern of heart disease in pregnancy in a Sri Lankan unit. Method: Consecutive patients with heart disease complicating pregnancy attending the University Obstetrics and Gynaecology Unit, Colombo were studied from 1 January 1993 to 31 July 1994. History, clinical evaluation and echocardiography were performed in all subjects to determine the cause and severity of heart disease. Cardiac and obstetric complications and pregnancy outcome were recorded prospectively. The data werecompared with those published from the same department on four previous occasions over the past four decades. Conclusions: Although there is an increase in incidence of heart disease complicating pregnancy over the previous 44 years, the proportion of patients with rheumatic heart disease has declined.There is a 6-fold rise in congenital heart disease. There is an increase in the diagnosis of mitral valve prolapse coinciding with the introduction of echocardiography. The maternal mortality rate remains high.